Relationship Between Shift Work and the Risk of Prostate Cancer: An Evidence Base Case Report - Irwan Suhadi; Indah Widyahening; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Prostate cancer has been associated with jobs that involve some degree of work at night. In 2007, the International Agency for Research on Cancer (IARC) concluded that shift work involving circadian disruption was probably carcinogenic in humans. Exposure to artificial LAN (Light at Night) suppresses pineal melatonin secretion and subsequently leads to an increase of sex hormones, which in turn could increase the susceptibility to hormone-dependent cancers. Disruption of the circadian rhythm regulated by several clock genes controlling apoptosis and cell proliferation, repeated phase shifting leading to internal desynchronisation and defects in the regulation of the circadian cell cycle, and also sleep deprivation alters immune function. In this case, the authors assessed the relationship between workers in a manufacture company who had worked shift work for 30 years and an increased risk of prostate cancer. This case takes evidence base from several journals that support this hypothesis while doing a critical appraisal to determine its validity and applicability.